Strategies to Enhance COVID-19 Vaccine Uptake among Prioritized Groups, Uganda—Lessons Learned and Recommendations for Future Pandemics - Kiiza, Daniel; Semanda, Judith Nanyondo; Wasswa, Christopher Kaliisa; Boore, Amy (Emerging Infectious Diseases, 2024)
COVID-19 vaccination was launched in March 2021 in Uganda and initially prioritized persons >50 years of age, persons with underlying conditions, healthcare workers, teachers, and security forces. However, uptake remained low 5 months after the program launch. Makerere University’s Infectious Diseases Institute supported Uganda’s Ministry of Health in optimizing COVID-19 vaccination uptake models by using point-of-care, place of worship, and place of work engagement and the Social Assistance Grant for Empowerment model in 47 of 135 districts in Uganda, where we trained influencers to support mobilization for vaccination outreach under each model. During July–December, vaccination rates increased significantly in targeted regions, from 92% to 130% for healthcare workers, 40% to 90% for teachers, 25% to 33% for security personnel, 6% to 15% for persons >50 years of age, and 6% to 11% for persons with underlying conditions. Our approach could be adopted in other targeted vaccination campaigns for future pandemics.